Engklek Edukasi: Fun Hopping, Learning To Follow Rules - Nur Fadhilah; Sahitya Indriati Pratiwi; Deni Zein Tarsidi (KOLABORASI: Journal of Multidisciplinary, 2024)
Character education is expected to be able to prepare Indonesia's golden generation in 2025 who are not only intelligent, but also have high morals and integrity. This research aims to develop the traditional game Engklek Patuh Aturan (EPA) as a Civics learning media that combines the fun of playing with character education. This study uses a qualitative approach, which describes and elaborates on the influence of the use of learning media in education. The data collection techniques were carried out through literature studies with several approaches. Furthermore, literature review from academic journals was also conducted, especially those that review the impact of games on children's social skills and compliance with rules. Then, a comparative approach was used by comparing literature on other traditional games in character education, so that similarities and differences in their impact can be seen. Based on the results of a review of various literatures, it can be synthesized that indeed the traditional games Engklek Patuh Aturan (EPA) are an effective traditional game for realizing national character values. Therefore, it is necessary to carry out a strategy of introducing traditional games for children by using it as the Civics Learning Media in introducing and instilling the value of nationalism. One alternative effort can be made to preserve traditional games that have various benefits for life.